Verbena officinalis (Common Vervain) – A Review on the Investigations of This Medicinally Important Plant Species - Kubica, Paweł; Szopa, Agnieszka; Dominiak, Jakub; Luczkiewicz, Maria; Ekiert, Halina (Planta Medica, 2020)
Verbena officinalis (common vervain) is a medicinal plant species widely distributed in the world and commonly used in folk medicine of different countries, including traditional Chinese medicine. Monographs on “Verbenae herba” have been included in the European Pharmacopoeia since 2008, and in the Chinese Pharmacopoeia since 1995. This work presents botanical characteristics of this species. It reviews the current knowledge of its chemical composition, which is a rich source mostly of iridoids, phenylpropanoid glycosides, phenolic acids, flavonoids, terpenoids, and essential oil. A large part of this article summarizes traditional medicinal uses and professional pharmacological in vitro and in vivo studies that prove new important applications, e.g., antioxidant, antimicrobial, anti-inflammatory, neuroprotective anticancer, analgesic, or anticonvulsant of verbena herb extracts and individual metabolites. Moreover, emphasis is put on the use of V. officinalis in the food and cosmetics industries, especially due to its antioxidant, antibacterial, and anti-inflammatory properties, and the presence of essential oil with an attractive fragrance composition. This paper also presents the state of biotechnological studies of this species.
Keywords: vervain; Verbena officinalis; Verbenaceae; chemical composition; therapeutic significance; investigation of biological activity; biotechnological research